Human resource management practices aimed at seeking the commitment of employees on financial and non-financial (subjetive) performance in spanish firms: an empirical contribution - Triguero Rafael (2012)
The purpose of this paper is to assess the relationship between Human Resource Management (HRM) practices and organizational performance in Spanish firms from a financial and non-financial perspective (subjective). The empirical study was conducted with a sample of 102 firms in the region of Andalucía (Spain). The results of statistical analysis have shown the fundamental role of establishing HRM practices aimed at seeking the employees' commitment and its positive influence on organizational performance. Results also showed that the subjective measures for organizational performance better explained this phenomenon of study.